Kolaborasi Pemberdayaan Masyarakat Berbasis Teknologi dan Kearifan Lokal di Desa Cipaku Kecamatan Ciamis - Nita Fauziah Oktaviani; Ali Akbar Hakim; Rai Amalia; Rahmi Bilqis Ramdani; Dea Nurlaila Lestari; Taofik, Taofik; Kurniawan Dwi Hartono; Nailah Nada Fadilah (Journal of Empowerment Community, 2026)
Community empowerment is a strategic approach to improving social welfare and fostering local economic independence through the utilization of village potential. The Community Service and Learning Program (KKN-PPM) conducted by Universitas Perjuangan Tasikmalaya in Cipaku Village, Ciamis Regency, aimed to strengthen local capacities and address multi-dimensional challenges faced by rural communities. This activity employed a participatory approach through observation, community discussions, potential mapping, and problem-based methods involving local stakeholders. The program covered six main sectors: education, health, economy, environment, institutional development, and disaster mitigation. Educational programs such as free tutoring, literacy corners, and agro-education improved students’ learning motivation and agricultural awareness. Health programs—including free medical check-ups, herbal medicine cultivation, and hygiene promotion—enhanced community well-being. Economic activities such as financial literacy seminars and digital business creation empowered local micro-entrepreneurs. Environmental and disaster mitigation programs encouraged eco-conscious behavior and preparedness for natural hazards. Overall, the KKN-PPM program effectively strengthened collaboration between students, the village government, and the community, fostering sustainable empowerment and local wisdom–based rural development.